FIRST COMPARATIVE MORPHOLOGICAL STUDY OF FASCIOLA HEPATICA (LINNAEUS, 1758) FROM BRAZIL AND ARGENTINA - de Assis Santos, Jéssica (2014)
Fascioliasis is an infection posing a substantial threat to public health, besides causing economic impacts due to its increasing prevalence in recent years. It is considered endemic in Peru and Bolivia and in Brazil's southern state of Rio Grande do Sul. Studies conducted with specimens of Fasciola hepatica from different geographic regions have shown that the characteristics of the adult worms and eggs vary according to host's distribution. In this study, we evaluated whether these variations also occur in specimens obtained from cattle bred in Brazil (Cordeiro in Rio de Janeiro state and Lavras in Minas Gerais) and Argentina (Catamarca and Salta provinces), using light microscopy and light microscopy with differential interference contrast. The results demonstrated differences in the specimens from each locale, mainly in the distribution and quantity of spines in the tegument. The integrated use of various microscopic techniques is necessary to gain a better understanding of the morphology of this parasite.